TEACHING WRITING SKILL ON RECOUNT TEXT BASED ON BRAINSTORMING IN THE CLASSROOM - Suhaimi Suhaimi (Ta'dib, 2016)
AbstractThe purpose of this article is to explain how to teach recount text in the classroom. The ability to write is one of the skills that should be taught in schools. Reality shows that there are many students who have problems in writing. The problems could be some students have limited ideas in writing. Furthermore, almost all of the students thought writing was boring, so they are not interested in writing. Then, writing is a difficult thing because they have to think about the selection of tenses and vocabulary correctly in a sentence. Considing facts, the author is interested in the theme of teaching the recount text-based brainstorming as one effective way to improve students' understanding in writing recount text. Brainstorming can increase students, creativity and to generate a lot of ideas in a short time, by extending the viewpoint of any aspects or thought .Keyword: writing, recount text, brainstorming